Belatacept-Based Maintenance Immunosuppression Controls the Post-Transplant Humoral Immune Response in Highly Sensitized Nonhuman Primates. Issue 12 (29th December 2022) - Schmitz, Robin; Fitch, Zachary W.; Manook, Miriam; Schroder, Paul M.; Choi, Ashley Y.; Olaso, Danae; Yoon, Janghoon; Bae, Yeeun; Shaw, Brian I.; Song, Mingqing; Kuchibhatla, Maragatha; Farris, Alton B.; et al.
Key Points: Belatacept-based maintenance immunosuppression prevents antibody-mediated rejection and enables long-term kidney allograft survival in sensitized nonhuman primate recipients. Post-transplant belatacept prevents the rebound of follicular helper T cells, class-switched B cells, and antibody-secreting cells. Additional belatacept with tacrolimus increases the risk of viral reactivation and post-transplant lymphoproliferative disease. Abstract : Preexisting donor-specific antibodies (DSA) to MHC antigens increase the risk of antibody-mediated rejection (AMR) in sensitized transplant recipients and reduces graft survival. Pretransplant desensitization with costimulation blockade and proteasome inhibition has facilitated transplantation in our preclinical nonhuman primate (NHP) model. However, long-term graft survival is limited by rebound of DSA after transplantation. In this study, we performed kidney transplants between highly sensitized, maximally MHC-mismatched NHPs ( n =14). At kidney transplantation, primates received T cell depletion with rhesus-specific anti-thymocyte globulin (rhATG; n =10) or monoclonal anti-CD4 and anti-CD8 antibodies ( n =4). Maintenance immunosuppression consisted of belatacept and tacrolimus ( n =5) or belatacept and rapamycin ( n =9) with steroids. Rebound of DSA post–kidney transplantation was significantly reduced compared with maintenance immunosuppression with tacrolimus, mycophenolate, and steroids. Protocol lymph node biopsy specimens showed a decrease in germinal center activity, with low frequencies of T follicular helper cells and class-switched B cells after kidney transplantation. Combined belatacept and rapamycin was superior in controlling viral reactivation, enabling weaning of ganciclovir prophylaxis. Tacrolimus was associated with increased morbidity that included cytomegalovirus and parvovirus viremia and post-transplant lymphoproliferative disorder. All primates in the tacrolimus/belatacept group failed discontinuation of antiviral therapy. Overall, belatacept-based immunosuppression increased AMR-free graft survival by controlling post-transplant humoral responses in highly sensitized NHP recipients and should be further investigated in a human clinical trial.